Factors Influencing on the Occurrence of Anemia in Pregnant Adolescents at Chaiya Hospital, Surat Thani Province - Juntarapimon, Panudda; Rakhab, Aranya; Thongwon, Thirawan (Princess of Naradhiwas University Journal, 2025)
This retrospective correlational predictive research aimed to explore factors influencing the occurrence of anemia in pregnant adolescents receiving prenatal care services at antenatal clinic, Chaiya Hospital, Surat Thani Province. Data were collected from the medical records of pregnant adolescents diagnosed with anemia. The sample size was calculated using the Krejcie and Morgan formula adjusted for a finite population, resulting in a sample of 97 cases from a population of 470, covering the fiscal years 2013–2023. The questionnaire comprising personal and health-related factors. Data analysis was performed using descriptive statistics and multiple regression analysis. The results revealed that factors significantly influencing the occurrence of anemia at a statistical significance level of .05 were age, pre-pregnancy body mass index (BMI), and occupation (student status). Age had a negative influence on anemia (β = -.379, p = .031), while pre-pregnancy BMI had a positive influence (β = .298, p = .004). Additionally, being a student had a negative influence on anemia (β = -.393, p = .038). The findings indicate that younger pregnant adolescents, particularly students with a low pre-pregnancy BMI, are at higher risk of developing anemia and require special attention regarding nutrition and timely access to healthcare services during pregnancy.